The Implementation of Police Reform in Bosnia and Herzegovina: Analysing UN and EU Efforts1. Issue 1 (28th January 2014) - Padurariu, Amelia
This article analyses the role of the main international actors involved in the implementation of police reform in post-conflict Bosnia and Herzegovina, notably that of the UN and the EU. Despite considerable efforts and resources deployed over 17 years, the implementation of police reform remains an 'unfinished business' that demonstrates the slow pace of implementing rule of law reforms in Bosnia's post-conflict setting, yet, in the long-term, remains vital for Bosnia's stability and post-conflict reconstruction process. Starting with a presentation of the status of the police before and after the conflict, UN reforms (1995–2002) are first discussed in order to set the stage for an analysis of the role of the EU in the implementation of police reform. Here, particular emphasis is placed on the institution-building actions of the EU police mission in Bosnia and Herzegovina deployed on the ground for almost a decade (2003-June 2012). The article concludes with an overall assessment of UN and EU efforts in post-conflict Bosnia and Herzegovina, including the remaining challenges encountered by the EU on the ground, as the current leader to police reform implementation efforts. More generally, the article highlights that for police reform to succeed in the long-term, from 2012-onwards, the EU should pay particular attention to the political level, where most of the stumbling blocks for the implementation of police reform lie.